Development Of Web-Based Teleradiology Application To Enhance The Quality Of Radiology Services - Eny Siswanti; A.Gunawan Santoso; Rini Indrati; Tri Asih Budiati; Rasyid Rasyid (International Journal of Medicine and Health, 2024)
The development of digital radiology technology improves the quality of medical services, but challenges in image distribution and interpretation encourage the use of teleradiology. The development of web-based teleradiology applications is a cost-effective solution with the ability to integrate patient data and DICOM image display to improve the efficiency of radiology interpretation. This has the potential to improve the quality of radiology services by accelerating the diagnostic process and reducing the physical accessibility limitations of radiologists.This study aims to develop a web-based application as a solution to radiographic image delivery and PACS weaknesses, and test its effectiveness in improving the quality of radiology services. The research method used is the research and development (R&D) method, which aims to produce and test new products. The results of this study show that the development of a web-based teleradiology application provides an appropriate solution to the constraints of the reader's presence at the image capture site, while maintaining image quality according to DICOM standards. The application allows easy use of various devices, data exchange between medical professionals, and secure data storage. In Addition, it reduces the waiting time in the delivery and reading of radiographic images by radiologists. Compared to older methods, such as delivery via email or Whatsapp, this web application shows improved quality and accuracy of radiographic image reading.